2021
DOI: 10.2196/27423
|View full text |Cite
|
Sign up to set email alerts
|

Availability, Formulation, Labeling, and Price of Low-sodium Salt Worldwide: Environmental Scan

Abstract: Background Regular salt is about 100% sodium chloride. Low-sodium salts have reduced sodium chloride content, most commonly through substitution with potassium chloride. Low-sodium salts have a potential role in reducing the population's sodium intake levels and blood pressure, but their availability in the global market is unknown. Objective The aim of this study is to assess the availability, formulation, labeling, and price of low-sodium salts curren… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 30 publications
2
47
2
Order By: Relevance
“…A range of 1-way sensitivity analyses were performed to test the robustness of base-case results. The variations included (1) using lowest, median, and highest market price for salt substitute in China 31 ; (2) using alternative discount rates of 0% and 8% as recommended by the Chinese Pharmacoeconomic Guidelines 16 ; (3) using lowest and highest unit prices for outpatient medication costs; (4) including only inpatient costs for health care costs; (5) assuming 0, 10%, and 30% of fatal events occurred at home with 0 inpatient health care costs; and (6) assigning inpatient costs for all hospitalizations, not just hospitalizations for cardiovascular causes. For the analyses of QALYs, we also assessed the effects of (7) using the lower and upper bounds of the 95% CI for the baseline HSU and (8) varying the HSU decrements applied by ±20%.…”
Section: Methodsmentioning
confidence: 99%
“…A range of 1-way sensitivity analyses were performed to test the robustness of base-case results. The variations included (1) using lowest, median, and highest market price for salt substitute in China 31 ; (2) using alternative discount rates of 0% and 8% as recommended by the Chinese Pharmacoeconomic Guidelines 16 ; (3) using lowest and highest unit prices for outpatient medication costs; (4) including only inpatient costs for health care costs; (5) assuming 0, 10%, and 30% of fatal events occurred at home with 0 inpatient health care costs; and (6) assigning inpatient costs for all hospitalizations, not just hospitalizations for cardiovascular causes. For the analyses of QALYs, we also assessed the effects of (7) using the lower and upper bounds of the 95% CI for the baseline HSU and (8) varying the HSU decrements applied by ±20%.…”
Section: Methodsmentioning
confidence: 99%
“…A recent research study showed that a range of modelled reduced-sodium salt strategies had the potential to be cost-effective in lowering blood pressure at a population level in Vietnam [ 18 ]. Despite reduced-sodium salts being effective and cost-effective, as demonstrated in trials and modelling studies, reduced-sodium salts are not widely available on the market and are more expensive than regular salts [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Low-sodium salt is not widely available on the global market, particularly in LMICs [ 35 ]. A recent study found that low-sodium salt is available in just under a quarter of all countries [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Low-sodium salt is not widely available on the global market, particularly in LMICs [ 35 ]. A recent study found that low-sodium salt is available in just under a quarter of all countries [ 35 ]. Production and regulatory challenges (e.g., development of national standards on low-sodium salt, consistent definitions of acceptable levels of sodium and potassium, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation